Analisis Microinteractions pada Aplikasi Manajemen Keuangan dengan Metode System Usability Scale - Ni Wayan Diyarini; I Gede Arta Wibawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Financial management is essential for personal financial well-being, yet financial literacy remains low in Indonesia. To improve usability, this study analyzes microinteractions in existing financial management applications by using System Usability Scale (SUS) methode. Through literature review, observation, and online surveys, microinteraction effectiveness is assessed, revealing areas for improvement. Results indicate a SUS score of 40, suggesting poor usability. Thus, redesigning the application is recommended to enhance usability and user experience, fostering better financial management practices.